-4(-6w+4)-3w=5(w-4)-6

Simple and best practice solution for -4(-6w+4)-3w=5(w-4)-6 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -4(-6w+4)-3w=5(w-4)-6 equation:


Simplifying
-4(-6w + 4) + -3w = 5(w + -4) + -6

Reorder the terms:
-4(4 + -6w) + -3w = 5(w + -4) + -6
(4 * -4 + -6w * -4) + -3w = 5(w + -4) + -6
(-16 + 24w) + -3w = 5(w + -4) + -6

Combine like terms: 24w + -3w = 21w
-16 + 21w = 5(w + -4) + -6

Reorder the terms:
-16 + 21w = 5(-4 + w) + -6
-16 + 21w = (-4 * 5 + w * 5) + -6
-16 + 21w = (-20 + 5w) + -6

Reorder the terms:
-16 + 21w = -20 + -6 + 5w

Combine like terms: -20 + -6 = -26
-16 + 21w = -26 + 5w

Solving
-16 + 21w = -26 + 5w

Solving for variable 'w'.

Move all terms containing w to the left, all other terms to the right.

Add '-5w' to each side of the equation.
-16 + 21w + -5w = -26 + 5w + -5w

Combine like terms: 21w + -5w = 16w
-16 + 16w = -26 + 5w + -5w

Combine like terms: 5w + -5w = 0
-16 + 16w = -26 + 0
-16 + 16w = -26

Add '16' to each side of the equation.
-16 + 16 + 16w = -26 + 16

Combine like terms: -16 + 16 = 0
0 + 16w = -26 + 16
16w = -26 + 16

Combine like terms: -26 + 16 = -10
16w = -10

Divide each side by '16'.
w = -0.625

Simplifying
w = -0.625

See similar equations:

| 8x+11=27 | | -4-(1)= | | 5(u+3)=-3(5u-9)+5u | | 63=3ab+3 | | t+8=-3 | | 2+4n=n+10 | | x+9/2=23/5-x-3/5 | | 65-40= | | 65(40)= | | 6x-16=43 | | 55-35= | | x-35=20 | | (8x+3)+6=2 | | 5(2x+8)-5x=(5x+6) | | 65/40= | | 6p - 5 = 2p + 7 | | 6p-5=2p+ 7 | | 6w/3=-4 | | 27x+1324=1999 | | -10/2= | | 6x-8=-2x | | 20+2m= | | 2m+8=20 | | 3(c-2)+5=2(c+1) | | n-4=-6 | | -8=-3 | | 100x-x=0 | | 5x-8-2x=4x-6 | | 15(26/25)+15q=-33 | | n-52=-3/2(18+n) | | 30+2x+5x=100 | | X=-46+8x |

Equations solver categories